Optimizing the Improvement of Judge Competence in Settlements of Sharia Economic Disputes in Religious Courts - Adelia, Deby; Yumarni, Ani; Suprijatna, Dadang (Batulis Civil Law Review, 2023)
Introduction: This is motivated by the increasingly widespread sharia economic disputes being handled by the Religious Courts, so that an institution is needed that can create the character of judges that are in accordance with the expectations of society. The institution is the Research and Development Agency for Legal and Judicial Education and Training of the Supreme Court of the Republic of Indonesia (Balitbang Diklat Kumdil MA-RI).Purposes of the Research: This paper describes the legal symptoms or legal facts related to the ability of religious court judges to decide cases related to sharia economics and studies the education and training curriculum for judges within the scope of the Supreme Court of the Republic of Indonesia No. 4 of 2019 concerning Procedures for Simple Claims and Supreme Court Regulation No. 14 of 2016 concerning Procedures for Settlement of Sharia Economic DisputesMethods of the Research: This paper uses a normative juridical approach.Results of the Research: Implementation of the curriculum at the Ministry of Education and Training Research and Development of the Supreme Court ‘Kumdil’ aims to improve the ability to organize training. The capacity building referred to is one of the certifications of sharia economic judges which is aimed at forming the quality of judges' resources in the technical field of justice who are professional, have integrity and are independent in resolving sharia economic disputes.